The Migraine Premonitory Phase. Issue 4 (August 2018) - Karsan, Nazia; Bose, Pyari; Goadsby, Peter J.
ABSTRACT: PURPOSE OF REVIEW: The premonitory phase of migraine is defined as the presence of nonpainful symptomatology occurring hours to days before the onset of headache. Symptoms can include neck stiffness, yawning, thirst, and increased frequency of micturition. Clinical recognition of these symptoms is important to ensure early and effective attack management. Further understanding of the clinical phenotype and neurobiological mediation of these symptoms is important in the advancement of therapeutics research in both acute and preventive treatments of migraine. RECENT FINDINGS: Since 2014, functional imaging studies have been conducted during the premonitory stage of migraine and have provided novel insights into the early neurobiology and anatomy of the earliest stage of the migraine attack. These studies have shown early involvement of subcortical brain areas including the hypothalamus, substantia nigra, dorsal pons, and various limbic cortical areas, including the anterior cingulate cortex during the premonitory phase. More recent work has revealed altered hypothalamic-brainstem functional connectivity during migraine, which starts before the onset of pain. These exciting findings have provided functional correlation of the symptoms experienced by patients and changes seen on functional brain imaging. SUMMARY: This article focuses on the prevalence, phenotype, and proposed neurobiology of premonitory symptomatology in migraineurs as well as the scope of future research.